Proof of Infringement in European Competition Law - de la Vega García, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The article analyzes the main legal issues related to the evidence of facts constituting an antitrust violation, considering competition rules and, especially, the jurisprudence developed within the European Union. It addresses the evidentiary challenges inherent in competition law infringements and the importance of safeguarding the rights of companies involved. In this context, the article examines key criteria for evidentiary analysis, including the subject matter of the evidence, the allocation of the burden of proof, the means and methods of evidence, as well as their assessment according to the standards established under European Union law